DEVELOPMENT OF PHYSICAL SCIENCES PROGRAM AT PINSTECH - Qureshi, I. H. (The Nucleus, 2020)
Pakistan Institute of Nuclear Science and Technology, established in 1965 is the premier research institute of PAEC in Physical Sciences. PINSTECH has undergone various phases of development during the last four decades the first decade was devoted to the development of infrastructure and establishment of R&D facilities, whereas the second decade saw both expansion and consolidation of R&D activities. In the second decade high priority was given to the R&D work directed towards technologically oriented goals without discouraging basic and applied research. Therefore, pilot plants were set up for the production of reactor-grade UO2 for fuel fabrication and for the extraction of zirconium from beach sand. A comprehensive program for physical and chemical characterization of materials was started. The expansion of R&D activities and upgradation of facilities continued in the third and fourth decades. Studies on a numbers of projects such as establishment of a miniature neutron source reactor, power upgradation and conversion of the research reactor fuel to low enriched uranium, fabrication of lasers and electro-optical devices, charged particle accelerator etc. have been completed and various new projects have been started. Studies on the corrosion of metals and alloy development, synthesis of special ion-exchange resins, production of radiopharmaceutical cold kits, development of laser land leveller and environmental monitoring constituted important parts of R&D activities. Over the years PINSTECH has made significant contributions in various programs of PAEC and in the international pool of knowledge, which have received both national and international recognition. The Islamic Development Bank, in recognition of its valuable scientific contributions awarded the first prize to PINSTECH in 2002. PINSTECH has played an important role in the development of science and technology in the country. The technical contributions have been made primarily through quality manpower, development of processes and products, specialized services and provision of research environment that encourages innovation.